Implementation of BWI Regulation Number 1 of 2020 on Productive Waqf Management at the Synergi Foundation Institution - Ahmad Ridwansah, Asep; Sunaryo Mukhlas, Oyo (Yayasan Mentari Madani, 2025)
This study aims to analyze the implementation of Indonesian Waqf Board (BWI) Regulation No. 01 of 2020 concerning the Management of Productive Waqf within the Sinergi Foundation, located in Bandung City. The regulation was issued as an operational guideline for nazhir (waqf managers) to manage waqf assets professionally, productively, and accountably. This research employs a qualitative approach using a case study method. Data collection techniques include observation, in-depth interviews, and document analysis. The findings reveal that the Sinergi Foundation has implemented the principles outlined in the BWI regulation effectively through an established institutional system, a social investment-based management strategy, and the application of transparent and digital-based governance. However, several challenges persist, such as the limited availability of professional human resources in waqf management and the need for more detailed derivative regulations. This study recommends enhancing nazhir capacity, strengthening monitoring systems, and expanding stakeholder collaboration to achieve sustainable and impactful productive waqf management for society